Development of Mo/γ-Al2O3-CeO2 catalyst with high thermal stability by modified impregnation method - Ramli, A. (Trans Tech Publications Ltd, 2017)
In the present studies, different characterization techniques have been utilized to correlate the physicochemical properties of the synthesized catalysts with their thermal stability. The results indicated that strong metal-support (Mo-support) interaction existed in the γ-Al2O3-CeO2 supported catalyst with higher CeO2 loading as compared to the Mo/γ-Al2O3 catalyst. This suggested that the addition of CeO2 into the γ-Al2O3 enhanced the metal-support interaction, thus decreases the reducibility, depending on the CeO2 loading. Similarly, the catalyst with higher CeO2 loading exhibited lower Ce 3d and higher Mo 3d binding energies respectively, supporting the TPR results. © 2017 Trans Tech Publications, Switzerland.